To find the values of \( x \) that make various equations equal to \( (x + 4)(x - 2) \), we first need to expand the expression \( (x + 4)(x - 2) \).
Expanding the expression:
\[ (x + 4)(x - 2) = x^2 - 2x + 4x - 8 \] \[ = x^2 + 2x - 8 \]
Now that we have \( (x + 4)(x - 2) = x^2 + 2x - 8 \), we can set this equal to different expressions to find the values of \( x \).
If you have specific equations in mind that you would like to set equal to \( x^2 + 2x - 8 \), please provide them, and I can help you solve for \( x \). For example, if you want to solve:
- \( x^2 + 2x - 8 = 0 \)
- \( x^2 + 2x - 8 = k \) for some constant \( k \)
Let me know the equations or scenarios you're interested in!